Predicting anti-gay prejudice based on sex knowledege and education - Isakson, Samantha Anne (2012)
Bullying of sexual minority students is an increasingly prevalent topic among school psychologists and educational personnel across the country. This study measured the variables of sex knowledge (as measured through the Sexual Knowledge and Attitude Test for Adolescents) and anti-gay prejudice (as measured through the Attitudes Toward Lesbians and Gay Men – Revised Edition). The results of this study found that sex education is significantly, negatively correlated to anti-gay prejudice. While causational relationships still need to be analyzed, this suggests that there is a significant relationship between sex education and anti-gay prejudice. Through additional analysis, it was also discovered that sex attitude (as measured through the Sexual Knowledge and Attitude Test for Adolescents) is significantly, negatively correlated to anti-gay prejudice; sex attitude is also significantly, positively correlated to sex knowledge. This study discusses further predictors and outcomes regarding the two variables (sex knowledge and anti-gay prejudice).